Unresearched psychological phenomena in educational communication - Ortiz Torres, Emilio Alberto (Pensando Psicología, 2017)
Purpose: The article aims to assess the importance of the scientific study of suggestion, interpersonal perception and rumor as psychological phenomena that affect educational communication. Topic: The subject that is being addressed is the existence and influence of such subjective phenomena in different educational contexts in which interpersonal communication takes place. Development: A theoretical analysis is carried out on educational communication as an interdisciplinary concept, due to existing confluences between psychology and education as independent disciplines, with its respective contents and scope. Its general theoretical foundations reflect the different epistemological positions that support it, from which we infer the richness of existing particular conceptions that have led to the attainment of novel scientific results and are widely applicable to educational practice. However, researchers have not delved into the study of phenomena present in any communicative process (such as intrapersonal level, suggestion, perception and rumor, which are present in such communicative process in the educational field), but are considered to be not significant or improper. Conclusions: Based on the assessment made, the importance of these present and latent phenomena in different expressions of educational communication are emphasized, as well as the relevance of studying their peculiarities and potentialities to intentionally incorporate them in the improvement of communication in the educational field.